First time in the college classroom : a guide for teaching assistants, instructors, and new professors at all colleges and universities - Clement, Mary C. (Rowman & Littlefield Education, 2010)
People who teach in higher education are subject matter specialists, but they often have little preparation in how to teach. This book presents the knowledge base of college teaching in a user-friendly, easy-to-read, yet well-researched format. From sample syllabi to the creation of an effective grading scale, this book covers critically important aspects of organizing and teaching your curriculum. Suggestions for preparing for the first day of the semester will make all semesters run more smoothly. Chapters about building positive student relationships, student incivility, and academic integ.